Literation And Financial Inclusion Among Creative Economic MSMEs; A Comparative Study - Layaman Layaman; Robbani Robbani; Fella Hafidza (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
AbstractMicro, Small and Medium Enterprises are considered as sectors that are able to survive in the face of the economic crisis shock. However, there are some problems in running this Micro and Small and Medium Enterprises. This research is motivated by problems that hamper this development including limited management of financial management, human resources and access to capital. This is thought to have occurred because of low financial literacy among Small and Medium Enterprises. Therefore, this study aims to determine the condition and compare financial literacy and inclusion that is believed to help in the business development of the Creative Culinary Subsector of Micro Small and Medium Enterprises in the City of Cirebon with Cirebon Regency.The population in this study was 24,861 Micro Small and Medium Enterprises and 100 respondents. The sampling technique used purposive sampling with a sample size of 200 respondents or around 100 respondents in Cirebon City and 100 respondents in Cirebon Regency. While the analysis technique in this study uses multiple linear regression analysis with the help of SPSS Version 2.1The results of this study that the variable Literacy and Financial Inclusion significantly influence the Development of Culinary Subsectors of the Creative Economy of Small and Medium Enterprises in the City and District of Cirebon. The comparative value is that the condition of Financial Literacy or Inclusion in the Cirebon City region is greater than in Cirebon Regency.Â Keywords: Financial Literacy, Financial Inclusion, Micro, Small and Medium Enterprises